AMELIORATIVE EFFECTS OF ANGIOTENSIN RECEPTOR BLOCKERS AGAINST SCOPOLAMINE-INDUCED MEMORY IMPAIRMENT IN RATS - Deb, Debasree; Nayak, Veena; KURADY, LAXMINARAYANA BAIRY; Rao, Mohandas (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The present study was designed to investigate the cognitive enhancing property of angiotensin receptor blockers (ARBs) in scopolamineinduced amnesic rats. Methods: A total of 42 male Wistar rats were divided into seven groups. Group 1 received 2% gum acacia orally for 4 weeks, Group 2 received normal saline, and Group 3 received scopolamine (2 mg/kg/i.p.) as a single dose. Groups 4 and 5 received telmisartan (1.80 mg/kg and 3.60 mg/kg, respectively) while Groups 6 and 7 received losartan (2.25 mg/kg and 4.50 mg/kg, respectively), orally for 4 weeks, followed by scopolamine (2 mg/kg/i.p.) given 45 minutes prior to experimental procedure. Evaluation of learning and memory was assessed by using morris water maze test followed by estimation of hippocampal choline acetyltransferase (ChAT) activity. Alterations in hippocampal morphology and degree of neuronal survival were also analyzed following drug treatments. Results: Scopolamine-induced marked impairment of memory in the behavioral test which correlated with reduced ChAT activity and morphological changes in the hippocampus. Treatment with higher doses of telmisartan and losartan improved memory deficits in scopolamine-induced amnesic rats while increasing the hippocampal ChAT activity. The treatments also attenuated hippocampal degeneration and increased the number of surviving neurons in hippocampus scopolamine-induced amnesic rats. Conclusion: Pre-treatment with ARBs attenuated scopolamine-induced memory deficits which may be attributed to their angiotensin receptor blockade property or to improved cholinergic activity, and thus highlighting the potential of these drugs in dementia. Keywords: Angiotensin scopolamine, Amnesia, Angiotensin receptor blockers, Losartan, telmisartan